Atmospheric Cues and Sales Promotion Effects on Impulse Buying Behaviour in TikTok Live Fashion Shopping: The Role of Flow Experience and Time Pressure - Khadijah Nurul Aini; Nur Afifah; Ilzar Daud; Bintoro Bagus Purmono; Harry Setiawan (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of atmospheric cues and sales promotion on impulse buying behaviour, mediated by flow experience and moderated by time pressure in TikTok Live fashion in Indonesia. Using the SOR framework with a quantitative approach, 350 respondents were surveyed and analyzed using SmartPLS 4. Atmospheric cues and sales promotion positively and significantly affect flow experience and impulse buying behaviour, with flow experience as a partial mediator, while time pressure did not moderate the relationships. These findings emphasize that atmosphere quality and promotion in live streaming shape consumers' psychological state that drives impulse buying without time pressure.